1987
DOI: 10.1177/00220345870660030501
|View full text |Cite
|
Sign up to set email alerts
|

Potential Retinal Hazards of Visible-light Photopolymerization Units

Abstract: We evaluated the potential for retinal damage, both thermal and photochemical, from commercially available visible-light photopolymerization units. The spectral radiance profiles of 11 visible-light photopolymerization units were measured by means of a spectroradiometer and the results weighted according to the American Conference of Governmental Industrial Hygienists (ACGIH) Blue Light Hazard Function and Thermal Hazard Function. The values were then integrated by means of the proposed ACGIH hazard formulae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…122 Previous studies in the 1980's that assessed the hazards from QTH curing lights found that these units had little potential to cause ocular injury. 125,126 However, most lights studied in the 1980's delivered less than 400 mW/ cm 2 over a broad spectral range between 400 and 500 nm. Contemporary QTH, high power plasma arc (PAC), and LED curing lights may deliver much higher irradiances, (up to and greater than 5,800 mW/cm 2 ) and in some lights the peak spectral emission is close to 440 nm.…”
Section: Ocular Hazards: Blue Light Hazardmentioning
confidence: 99%
“…122 Previous studies in the 1980's that assessed the hazards from QTH curing lights found that these units had little potential to cause ocular injury. 125,126 However, most lights studied in the 1980's delivered less than 400 mW/ cm 2 over a broad spectral range between 400 and 500 nm. Contemporary QTH, high power plasma arc (PAC), and LED curing lights may deliver much higher irradiances, (up to and greater than 5,800 mW/cm 2 ) and in some lights the peak spectral emission is close to 440 nm.…”
Section: Ocular Hazards: Blue Light Hazardmentioning
confidence: 99%
“…Although most PDT applications are associated with a laser light, nonlaser light sources have also been used. Studies developed in the last decade clearly indicate that the use of the visible‐light isolated from a HHP unit (nonlaser light source) does not induce any thermal or photochemical damage to the retina [13]. In addition to that, the cost of use of HHP is lower than that of a laser light.…”
Section: Background Theory and Prelaboratory Preparationmentioning
confidence: 99%
“…The effects of thermal injury are most profound from short wavelength (from 400 to 500 nm) light with the peak at 440 nm. In the spectral range between 380 and 500 nm, however, the effect of the retinal thermal hazard function is larger than the bluelight hazard function by a factor of 10 (Satrom et al 1987). The spectrum of E Retina irradiance showed a higher Ryer (1998). level than that of E Blue irradiance in Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The retinal thermal criteria are based on the studies of Sliney et al (2005), Satrom et al (1987), and ACGIH (2006) TLVs and BEIs. For optical sources, the retinal thermal hazard must be evaluated for a single exposure and the entire spectral range from 385 to 1,400 nm must be considered.…”
Section: Retina Thermal Hazardmentioning
confidence: 99%